Common fixed points for some generalized nonexpansive mappings and nonspreading-type mappings in uniformly convex Banach spaces - Inthakon,W. (Springer Publishing Company, 2015)
In this article, we study the fixed point theorems for nonspreading mappings, defined by Kohsaka and Takahashi, in Banach spaces but using the sense of norm instead of using the function φ. Furthermore, we prove a weak convergence theorem for finding a common fixed point of two quasi-nonexpansive mappings having demiclosed property in a uniformly convex Banach space. Consequently, such theorem can be deduced to the case of the nonspreading type mappings and some generalized nonexpansive mappings. © 2012 Inthakon et al.; licensee Springer.